2010
DOI: 10.1159/000255141
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia for Behavioral Disturbances in Frontotemporal Dementia and Corticobasal Syndrome: A Voxel-Based Morphometry Study

Abstract: Background: Patients with syndromes of the frontotemporal dementia spectrum are frequently unaware of their behavioral changes. Methods: Seventy patients with a clinical diagnosis of behavioral variant frontotemporal dementia (bv-FTD, n = 27), aphasic variant frontotemporal dementia (a-FTD, n = 12) and corticobasal syndrome (CBS, n = 31) participated in the study. Anosognosia for behavioral disturbances was measured as discrepancy between caregiver’s and patient’s ratings on the Frontal Systems Behavior Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 76 publications
4
42
0
Order By: Relevance
“…In our study, while the median anosognosia scores were –1 (range –3 to 0) in HT patients, the scores were –1 (range –4 to 3) and 4.5 (range 3–18) in ALS patients without and with FTLD, respectively, with a significant difference between the groups. This result is in agreement with the finding of Zamboni et al [15] that patients with a behavioral variant of FTD (bv-FTD) underestimated their level of behavioral disturbance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, while the median anosognosia scores were –1 (range –3 to 0) in HT patients, the scores were –1 (range –4 to 3) and 4.5 (range 3–18) in ALS patients without and with FTLD, respectively, with a significant difference between the groups. This result is in agreement with the finding of Zamboni et al [15] that patients with a behavioral variant of FTD (bv-FTD) underestimated their level of behavioral disturbance.…”
Section: Discussionsupporting
confidence: 93%
“…The anosognosia scale [8] is so simple that patients with severe physical disability are able to complete the tests, whereas completion of the MMSE and FAB are limited to certain patients. Several tests have been used to evaluate anosognosia, including the Frontal Systems Behavior Scale (FrSBe) and the Interpersonal Adjectives Scale [6,14,15]. Using the FrSBe, Woolley et al [6] found that ALS patients with FTD exhibited a profound lack of insight compared to those without FTD, and it is of interest that we found a similar result using the much simpler anosognosia scale.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Impaired awareness for behavioural deficits has been previously associated with right temporal atrophy (Zamboni and Wilcock, 2011;Sollberger et al, 2014). A proposed mechanism for this finding was that impaired empathy and understanding of others' minds, frequently associated with right temporal atrophy, affects the ability to understand others' reactions to one's inappropriate behaviour, and to update one's self-knowledge accordingly (Zamboni et al, 2010). Poor metacognitive awareness has been directly related to impaired empathy (O'Keeffe et al, 2007).…”
Section: Clinical Relevance To Neurodegenerative Diseasesmentioning
confidence: 99%
“…Patients with FTD with right frontal hypoperfusion experience more changes in their self-perceptions (Miller et al, 2001;Mendez and Shapira, 2005), and anosognosia for memory loss in patients with Alzheimer's disease is correlated with right dorsolateral PFC hypoperfusion (Reed et al, 1993). Some studies have also reported the involvement of atrophy in left orbitofrontal (Salmon et al, 2006;Shibata et al, 2008), and temporal and parietal regions (Ries et al, 2007;Zamboni et al, 2010).…”
Section: Introductionmentioning
confidence: 99%